Campylobacter jejuni acquire new host-derived CRISPR spacers when in association with bacteriophages harboring a CRISPR-like Cas4 protein - Hooton, Steven P.T.; Connerton, Ian F. (Frontiers, 2015)
Campylobacter jejuni is a worldwide cause of human diarrhoeal disease. Clustered Repetitively Interspaced Palindromic Repeats (CRISPRs) and associated proteins allow Bacteria and Archaea to evade bacteriophage and plasmid infection. Type II CRISPR systems are found in association with combinations of genes encoding the CRISPR-associated Cas1, Cas2, Cas4 or Csn2, and Cas9 proteins. C. jejuni possesses a minimal subtype II-C CRISPR system containing cas1, cas2, and cas9 genes whilst cas4 is notably absent. Cas4 proteins possess 5′-3′ exonuclease activity to create recombinogenic-ends for spacer acquisition. Here we report a conserved Cas4-like protein in Campylobacter bacteriophages that creates a novel split arrangement between the bacteriophage and host that represents a new twist in the bacteriophage/host co-evolutionary arms race. The continuous association of bacteriophage and host in the carrier state life cycle of C. jejuni provided an opportunity to study spacer acquisition in this species. Remarkably all the spacer sequences observed were of host origin. We hypothesize that Campylobacter bacteriophages can use Cas4-like protein to activate spacer acquisition to use host DNA as an effective decoy to bacteriophage DNA. Bacteria that acquire self-spacers and escape phage infection must overcome CRISPR-mediated autoimmunity either by loss of the interference functions leaving them susceptible to foreign DNA incursion or tolerate changes in gene regulation.